Steel plate and method for manufacturing the same

By optimizing the chemical composition and manufacturing process of the steel plate, the problem that the steel plate is difficult to improve collision characteristics after heat treatment after pressure forming is solved, and the steel plate still maintains excellent toughness and impact absorption capacity after forming.

CN116018416BActive Publication Date: 2025-04-29NIPPON STEEL CORPORATION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180054990.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-10-15
Filing Date
2021-10-15
Publication Date
2025-04-29
Estimated Expiration
2041-10-15

AI Technical Summary

Technical Problem

The prior art is difficult to improve collision characteristics by heat treatment after pressure forming of steel plates, and the martensite after processing and phase transitions induce the impact absorption capacity of the vehicle during collision.

Method used

By optimizing the chemical composition and manufacturing process of the steel plate, especially controlling the segregation of Mn and the distribution of residual austenite during hot rolling and annealing, and combining the cold rolling and heat homogenizing process, steel plates with excellent pressure forming and toughness are formed.

Benefits of technology

The steel plate remains excellent toughness after forming into a pressure component, and improves the impact absorption capacity during vehicle collisions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004111440470000301
    Figure BDA0004111440470000301
  • Figure BDA0004111440470000311
    Figure BDA0004111440470000311
  • Figure BDA0004111440470000321
    Figure BDA0004111440470000321
Patent Text Reader

Abstract

The present invention provides a steel plate having a predetermined chemical composition, wherein the microstructure at a depth of 1 / 4 of the plate thickness from the surface contains, by volume fraction, ferrite: 0% to 50%, retained austenite: 6% to 30%, bainite: 5% to 60%, tempered martensite: 5% to 50%, primary martensite: 0% to 10%, and pearlite: 0% to 5%, and at a depth of 1 / 4 of the plate thickness from the surface, the number ratio of the retained austenite having an aspect ratio of 2.0 or more in the entire retained austenite is 50% or more, and the number density of inclusions and precipitates having a grain size of 1 μm or more is 30 pieces / mm 2 Next, at a depth of 1 / 20 of the plate thickness from the surface, the average interval of Mn concentrated portions in a direction perpendicular to the rolling direction was 300 μm or less, and the standard deviation of the Mn concentration in the retained austenite was 0.40% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a steel plate and a method for manufacturing the same.

[0002] This application claims priority based on Japanese Patent Application No. 2020-174217 filed on October 15, 2020, the contents of which are cited here. Background Art

[0003] In recent years, from the perspective of greenhouse gas emission restrictions accompanying global warming countermeasures, it is required to improve the fuel efficiency of automobiles. In order to reduce the weight of the vehicle body and ensure collision safety, the application of high-strength steel sheets is expanding. In particular, the demand for high-strength steel sheets with a tensile strength of 980 MPa or more is rising recently.

[0004] High-strength steel sheets for automobile parts require not only strength but also properties necessary for forming parts, such as press formability. Strength and press formability are in a trade-off relationship, but TRIP steel sheets (TRansformation Induced Plasticity) that utilize the transformation induced plasticity of retained austenite are known as a means of achieving both of these properties.

[0005] In addition, collision characteristics are important when the vehicle is actually running. Regarding the collision characteristics, toughness and bendability after pre-strain is given by press forming and heat treatment is performed in the painting and baking process are important.

[0006] Patent Documents 1 and 2 disclose a technology for high-strength TRIP steel sheets with improved elongation and hole expansion ratio by controlling the volume fraction of the microstructure within a predetermined range. Patent Document 3 discloses a technology for obtaining excellent hole expansion and bendability, low-temperature embrittlement resistance, and 0.2% yield strength by controlling the area fraction and morphology of retained austenite and bainitic ferrite within a predetermined range in a high-strength steel sheet of 980 MPa or more.

[0007] Patent Document 4 discloses a technique for improving the formability of a high-strength steel sheet by performing multiple annealing to reduce the elongated tempered martensite to less than 20% while retaining a retained austenite phase.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: International Publication No. 2013 / 051238

[0011] Patent Document 2: Japanese Patent Application Publication No. 2006-104532

[0012] Patent Document 3: International Publication No. 2019 / 186989

[0013] Patent Document 4: Japanese Patent Application Publication No. 2013-185196 Summary of the invention

[0014] Problems to be solved by the invention

[0015] In any of the above-mentioned prior art documents, the press formability and toughness of the steel sheet after manufacturing are discussed, but no technology related to the steel sheet that is subjected to heat treatment in the baking process after press forming is disclosed to improve the collision characteristics. In addition, the martensite transformed from the retained austenite by the process-induced phase transformation deteriorates the toughness, thereby reducing the impact absorption energy of the components during the vehicle collision. In other words, although the above-mentioned prior art discloses the technology to improve the toughness of the steel sheet itself, in the above-mentioned prior art, there is still room for improvement in the technology to reduce the influence of the martensite after the process-induced phase transformation that deteriorates the collision characteristics of the actual vehicle.

[0016] An object of the present disclosure is to provide a steel sheet having excellent press formability and excellent toughness even after being baked and coated after being formed into a press component, and a method for producing the same.

[0017] Means for solving problems

[0018] The present inventors have studied a steel sheet having excellent press formability and excellent toughness even after being formed into a press component and then baked and coated, and a method for manufacturing the same. As a result, the following insights (i) to (iii) were obtained. In addition, it was found that the following insights (i) to (iii) can ensure the effects of high strength and improved formability based on the TRIP effect while suppressing the decrease in toughness caused by the primary martensite generated by the processing-induced phase transformation.

[0019] (i) The distribution state of retained austenite in the steel sheet structure is affected by the segregation of austenite-forming elements, namely Mn. Such Mn segregation is mainly generated during the solidification process in the casting process, and is caused by the element distribution in the solid-liquid coexistence area when the dendrite arm grows. This solidification segregation occurs when the slab is reheated in the hot rolling process to become a hot-rolled steel sheet, and the Mn concentration is distributed in the plate thickness direction and the plate width direction. Mn is a representative substitutional element, and homogenization in the single diffusion requires more than 24 hours at a high temperature of more than 1200°C. Therefore, it is difficult to significantly improve it through the cold rolling process and annealing process after ordinary hot rolling. Therefore, even in the finished plate, Mn segregation remains in the form of a band, and as a result, the retained austenite exists in the form of a band along the area with high Mn concentration. Then, since the retained austenite becomes martensite through processing-induced phase transformation in the press forming process, the toughness of the part is greatly deteriorated due to the banded martensite. Therefore, in order to improve the toughness of parts while achieving both high strength and excellent formability, it is necessary to improve the segregation of Mn in the process up to forming a hot-rolled steel sheet.

[0020] (ii) It is not easy to completely eliminate the Mn segregation in industry only by alleviating the Mn segregation in the previous stage of the hot rolling process such as (i) above. Therefore, it is necessary to make the retained austenite more evenly dispersed by microstructure control in the hot rolling process and the annealing process. Usually, when the microstructure control is performed by annealing after cold rolling, the phase transformation in the cooling from the highest heating temperature develops unevenly. As a result, the distribution of the retained austenite remaining as a non-transformed area becomes uneven due to the deviation to the segregation part of Mn. The reason is that the cold rolling performed when the cold-rolled steel sheet is usually manufactured is used to impart strain to the steel sheet, so that the recrystallization of ferrite produced in the heating in the annealing process and the reverse phase transformation to austenite become uneven. In contrast, by coiling or intermediate annealing, the microstructure before the final annealing is mainly composed of lath-shaped bainite or martensite, which is not subsequently given strain or suppressed strain due to cold rolling, etc., and annealing (final annealing) is performed in this state, thereby suppressing recrystallization during heating and maintaining the needle-shaped structure derived from the lath. In addition, since the bainite or martensite before the final annealing has a high dislocation density, Mn diffusion can be promoted via dislocation during annealing heating. As a result, the Mn concentration in austenite can be homogenized, and the Mn concentration distribution in the residual austenite remaining after cooling after annealing can be homogenized.

[0021] (iii) In addition to homogenizing the retained austenite, it is also important to reduce the inclusions in the steel as much as possible. The effect of inclusions on the toughness after forming into parts (after part forming, i.e., after press forming and baking and painting) was investigated, and the results showed that inclusions with a size of 1 μm or more had an adverse effect. In other words, by reducing inclusions of 1 μm or more, the toughness of the part after forming can be improved.

[0022] The present disclosure has been achieved based on the above-mentioned findings, and specifically has the following configuration.

[0023] [1] A steel plate, wherein the chemical composition comprises, in mass%, C: 0.150% to 0.400%, Si: 0.01% to 2.50%, Mn: 1.50% to 3.50%, P: 0.050% or less, S: 0.0100% or less, Al: 0.001% to 1.500%, Si and Al: 0.50% to 3.00% in total, N: 0.0100% or less, O: 0.0100% or less, Ti: 0% to 0.200%, V: 0% to 1.00%, Nb: 0% to 0.100%, Cr: 0% to 2.00%, Ni: 0% to 1.00%, Cu: 0% to 1.00%, Co: 0% to 1 .00%, Mo: 0% to 1.00%, W: 0% to 1.00%, B: 0% to 0.0100%, Sn: 0% to 1.00%, Sb: 0% to 1.00%, Ca: 0% to 0.0100% 、Mg: 0%~0.0100%, Ce: 0%~0.0100%, Zr: 0%~0.0100%, La: 0%~0.0100%, Hf: 0%~0.0100%, Bi: 0%~0.0100% and REM other than Ce and La: 0%~0.0100%, the remainder includes Fe and impurities; the microstructure at a depth of 1 / 4 of the plate thickness from the surface contains, by volume fraction, ferrite: 0% ~50%, retained austenite: 6%~30%, bainite: 5%~60%, tempered martensite: 5%~50%, fresh martensite: 0%~10%, pearlite: 0%~5%; at a depth of 1 / 4 of the plate thickness from the surface, the number ratio of the retained austenite with an aspect ratio of 2.0 or more in the total retained austenite is 50% or more, and the number density of inclusions and precipitates with a grain size of 1 μm or more is 30 pieces / mm 2 at a depth of 1 / 20 of the plate thickness from the surface, the average interval of the Mn concentrated portion in the direction perpendicular to the rolling direction is 300 μm or less, and the standard deviation of the Mn concentration in the retained austenite is 0.40% or less.

[0024] [2] The steel sheet according to [1] above, wherein the Vickers hardness Hv at a depth of 30 μm from the surface is sur The ratio of the hardness [Hv] to the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface may satisfy the following formula (1).

[0025] Hv sur / [Hv]≤0.80 (1)

[0026] [3] The steel sheet according to [1] or [2] above, which may have a plating layer on the surface.

[0027] [4] A method for manufacturing a steel plate, which is the method for manufacturing a steel plate described in [1], comprising the following steps: a casting step, wherein the molten steel having the chemical composition described in [1] is cast into a slab having a thickness of 200 to 300 mm; a hot rolling step, wherein the slab is hot-rolled to form a hot-rolled steel plate; a coiling step, wherein the hot-rolled steel plate is coiled at a temperature of 25 to 680°C; and a cold rolling step, wherein the hot-rolled steel plate after the coiling step is heated to a temperature of 20% or more. The invention relates to a method for forming a cold-rolled steel sheet by cold rolling at a reduction rate of 100 to 1000 seconds; a first annealing step, wherein the cold-rolled steel sheet is subjected to a first annealing; a second annealing step, wherein the cold-rolled steel sheet after the first annealing step is subjected to a second annealing; and a soaking step, wherein the cold-rolled steel sheet after the second annealing step is maintained at a temperature range of 260 to 450° C. for 10 to 1000 seconds; in the casting step, the solidification rate at a depth of 10 mm from the surface of the molten steel is set to 100 to 100 0°C / min, and the amount of molten steel poured per unit time is set to 2.0-6.0 tons / min, and the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the surface of the molten steel is set to be 4°C / sec or more for cooling; in the hot rolling process, the average heating rate of the slab between Ac1 and Ac1+30°C is 2-50°C / min, and the slab is heated at 1200°C or more for more than 20 minutes before hot rolling; In the first annealing process, the average heating rate between Ac1 and Ac1+30°C is above 0.5°C / second, and the maximum heating temperature of Ac3 to 950°C is maintained for 1 second to 1000 seconds, and the average cooling rate in the temperature range to 650°C is above 1°C / second, and the cooling stop temperature is 25 to 450°C; in the second annealing process, after maintaining the maximum heating temperature above Ac1+20°C and lower than Ac3 for 1 second to 1000 seconds, it is cooled to below 250°C.

[0028] [5] A method for manufacturing a steel plate, which is the method for manufacturing a steel plate described in [1], comprising the following steps: a casting step of casting molten steel having the chemical composition described in [1] into a slab having a thickness of 200 to 300 mm; a hot rolling step of forming a hot-rolled steel plate by hot rolling the slab; a coiling step of coiling the hot-rolled steel plate in a temperature range of 25 to 450° C.; a cold rolling step of forming a cold-rolled steel plate by cold rolling the hot-rolled steel plate at a reduction ratio of 30% or less as required; a first annealing step of performing a first annealing on the hot-rolled steel plate or the cold-rolled steel plate; and a soaking step of holding the hot-rolled steel plate or the cold-rolled steel plate after the first annealing step in a temperature range of 260 to 450° C. for 10 to 1000 seconds; in the casting step, a hot-rolled steel plate 10 mm above the surface of the molten steel is heated to 100° C. and heated to 1000 seconds. The solidification rate at the depth position is set to 100-1000°C / min, and the molten steel pouring amount per unit time is set to 2.0-6.0 tons / min, and the average cooling rate between the liquidus temperature and the solidus temperature of the surface part at a depth of 5 mm from the surface of the molten steel is set to 4°C / sec or more for cooling; in the hot rolling process, the average heating rate of the slab between Ac1 and Ac1+30°C is 2-50°C / min, and the slab is hot rolled after being heated at above 1200°C for more than 20 minutes, and after finishing rolling at a temperature above 850°C, it is cooled at an average cooling rate of 10°C / sec or more to 600°C; in the first annealing process, after maintaining at a maximum heating temperature above Ac1+20°C and below Ac3 for 1 second to 1000 seconds, it is cooled to below 250°C.

[0029] [6] The method for manufacturing a steel sheet according to [4] above, wherein in at least one of the first annealing step and the second annealing step, when the maximum heating temperature is maintained for 1 second to 1000 seconds, the atmosphere log (PH 2 O / PH 2 ) can also be -1.10≤log(PH 2 O / PH 2 )≤-0.07.

[0030] [7] The method for manufacturing a steel sheet according to [5] above, wherein in the first annealing step, when the maximum heating temperature is maintained for 1 second to 1000 seconds, the atmosphere log (PH 2 O / PH 2 ) can also be -1.10≤log(PH 2 O / PH 2 )≤-0.07.

[0031] [8] The method for manufacturing a steel sheet according to the above-mentioned [4] or [6] may also include a hot-dip galvanizing step, which is formed into a hot-dip galvanized steel sheet by immersing the cold-rolled steel sheet in a hot-dip galvanizing bath during the cooling from the maximum heating temperature to below 250°C in the second annealing step before the soaking treatment step.

[0032] [9] The method for manufacturing a steel sheet according to [5] or [7] above, wherein the method may also include a hot-dip galvanizing step, which is performed before the soaking step and during the cooling from the maximum heating temperature to below 250°C in the first annealing step to form a hot-dip galvanized steel sheet.

[0033]

[10] The method for manufacturing a steel sheet according to [4] or [6] above may further include a hot dip galvanizing step of forming a hot dip galvanized steel sheet by immersing the cold rolled steel sheet after the soaking treatment step in a hot dip galvanizing bath.

[0034]

[11] The method for manufacturing a steel sheet according to [5] or [7] above may also include a hot dip galvanizing step, in which the hot dip galvanized steel sheet is formed by immersing the hot rolled steel sheet or the cold rolled steel sheet after the soaking treatment step in a hot dip galvanizing bath.

[0035] Effects of the Invention

[0036] According to the present disclosure, it is possible to obtain a steel sheet that is excellent in press formability and has excellent toughness even after press forming and bake coating. DETAILED DESCRIPTION

[0037] An embodiment of the present disclosure relates to a steel plate, wherein the chemical composition comprises, in mass %, the following:

[0038] C: 0.150%~0.400%,

[0039] Si: 0.01% to 2.50%,

[0040] Mn: 1.50% to 3.50%,

[0041] P: 0.050% or less,

[0042] S: 0.0100% or less,

[0043] Al: 0.001% to 1.500%,

[0044] Si and Al: 0.50% to 3.00% in total,

[0045] N: 0.0100% or less,

[0046] O: 0.0100% or less,

[0047] Ti: 0% to 0.200%,

[0048] V: 0%~1.00%,

[0049] Nb: 0% to 0.100%,

[0050] Cr: 0% to 2.00%,

[0051] Ni: 0% to 1.00%,

[0052] Cu: 0% to 1.00%,

[0053] Co: 0% to 1.00%,

[0054] Mo: 0% to 1.00%,

[0055] W: 0%~1.00%,

[0056] B: 0%~0.0100%,

[0057] Sn: 0% to 1.00%,

[0058] Sb: 0% to 1.00%,

[0059] Ca: 0% to 0.0100%,

[0060] Mg: 0% to 0.0100%,

[0061] Ce: 0%~0.0100%,

[0062] Zr: 0% to 0.0100%,

[0063] La: 0% to 0.0100%,

[0064] Hf: 0%~0.0100%,

[0065] Bi: 0% ~ 0.0100%, and

[0066] REM other than Ce and La: 0% to 0.0100%,

[0067] The remainder includes Fe and impurities;

[0068] The microstructure at a depth of 1 / 4 of the plate thickness from the surface contains, by volume fraction: ferrite: 0% to 50%,

[0069] Retained austenite: 6% to 30%,

[0070] Bainite: 5% ~ 60%,

[0071] Tempered martensite: 5%~50%,

[0072] Primary martensite: 0%~10%,

[0073] Pearlite: 0% to 5%;

[0074] At a depth of 1 / 4 of the plate thickness from the surface, the number ratio of the retained austenite with an aspect ratio of 2.0 or more in the total retained austenite is 50% or more, and the number density of inclusions and precipitates with a grain size of 1 μm or more is 30 pieces / mm 2 the following;

[0075] At a depth of 1 / 20 of the plate thickness from the surface (position of 1 / 20 thickness), the average interval of Mn concentrated portions in a direction perpendicular to the rolling direction was 300 μm or less, and the standard deviation of the Mn concentration in retained austenite was 0.40% or less.

[0076] "Chemical composition"

[0077] First, the reasons for the above-mentioned limitation of the chemical composition of the steel sheet according to the embodiment of the present disclosure will be described. In the present specification, "%" that specifies the chemical composition means "mass %" unless otherwise specified.

[0078] [C: 0.150%~0.400%]

[0079] C (carbon) is an essential element for ensuring the strength of the steel plate. By setting the C content to 0.150% or more, the desired high strength can be obtained. The C content may be 0.170% or more or 0.180% or more. In addition, in order to ensure workability and weldability, the C content is set to 0.400% or less. The C content may also be 0.380% or less, 0.340% or less, or 0.300% or less.

[0080] [Si: 0.01% to 2.50%]

[0081] Si (silicon) is an element that inhibits the formation of iron carbides and contributes to improving strength and formability by leaving residual austenite. In order to obtain this effect, the Si content is set to 0.01% or more. The Si content may also be 0.05% or more, 0.10% or more, or 0.12% or more. In addition, in order to ensure the weldability of the steel plate, the Si content is set to 2.50% or less. The Si content may also be 2.40% or less, 2.20% or less, or 2.00% or less.

[0082] [Mn: 1.50% to 3.50%]

[0083] Mn (manganese) is a strong austenite stabilizing element and an element effective for increasing the strength of the steel plate. In order to obtain these effects, the Mn content is set to 1.50% or more. The Mn content may also be 1.60% or more, 1.70% or more, 1.90% or more, or 2.10% or more. In addition, in order to ensure weldability and low temperature toughness, the Mn content is set to 3.50% or less. The Mn content may also be 3.40% or less, 3.20% or less, or 3.00% or less.

[0084] [P: 0.050% or less]

[0085] P (phosphorus) is a solid solution strengthening element and is an element effective for increasing the strength of steel plates, but excessive inclusion deteriorates weldability and toughness. Therefore, the P content is set to 0.050% or less. Preferably, it is 0.045% or less, 0.035% or less, or 0.020% or less. It is preferred that the P content is small and may be 0%, but if the P content is extremely reduced, the cost of removing P increases. Therefore, from the perspective of economic efficiency, it is preferred that the lower limit of the P content be set to 0.001%.

[0086] [S: 0.0100% or less]

[0087] S (sulfur) is an element contained as an impurity, and is an element that deteriorates toughness and hole expansion by forming MnS in steel. Therefore, as a range in which the deterioration of toughness or hole expansion is not significant, the S content is set to 0.0100% or less. Preferably, it is 0.0050% or less, 0.0040% or less, or 0.0030% or less. It is preferred that the S content is small, and it can also be 0%, but if the S content is extremely reduced, the desulfurization cost increases. Therefore, from the perspective of economy, it is preferred to set the lower limit of the S content to 0.0001%.

[0088] [Al: 0.001%~1.500%]

[0089] Al (aluminum) is an element that can be used for steel deoxidation. Like Si, it is an effective element for inhibiting the formation of iron carbides and retaining residual austenite. Therefore, the Al content is set to more than 0.001%. The Al content can also be set to more than 0.005%, more than 0.010%, more than 0.025%, more than 0.050% or more than 0.100%. On the other hand, even if Al is contained excessively, the effect is saturated, which not only causes cost increase in vain, but also increases the load during hot rolling due to the increase in the phase transformation temperature of the steel. Therefore, the Al content is set to less than 1.500%. The Al content is preferably less than 1.200%, less than 1.000% or less than 0.800%.

[0090] [Si and Al: 0.50% to 3.00% or less in total]

[0091] Si and Al are useful elements for the industrial manufacture of TRIP steel sheets. By containing Si and / or Al, the formation of iron carbides in austenite with an increased C concentration can be suppressed, and stable residual austenite can be obtained even at room temperature. In order to obtain this effect, after setting the Si content and the Al content to the above range, the total content of Si and Al needs to be 0.50% or more. The total content of Si and Al is preferably 0.80% or more, more preferably 1.20% or more. On the other hand, excessive content deteriorates other properties such as castability and weldability during casting. Therefore, the total content of Si and Al is set to 3.00% or less. The total content of Si and Al is preferably 2.80% or less, more preferably 2.50% or less, and further preferably 2.00% or less.

[0092] [N: 0.0100% or less]

[0093] N (nitrogen) is an element contained as an impurity. If its content exceeds 0.0100%, it forms coarse nitrides in steel and deteriorates bendability and hole expansion. Therefore, the N content is set to 0.0100% or less. The N content is preferably 0.0080% or less, 0.0060% or less, or 0.0050% or less. It is preferred that the N content is small and can be 0%, but if the N content is extremely reduced, the cost of removing N increases. Therefore, from the perspective of economic efficiency, it is preferred to set the lower limit of the N content to 0.0001%.

[0094] [O: 0.0100% or less]

[0095] O (oxygen) is an element contained as an impurity. If its content exceeds 0.0100%, it forms coarse oxides in steel and deteriorates bendability and hole expansion. Therefore, the O content is set to 0.0100% or less. The O content is preferably 0.0080% or less, 0.0060% or less, or 0.0050% or less. The N content is preferably small and may be 0%, but from the viewpoint of manufacturing cost, the lower limit of the O content is preferably set to 0.0001%.

[0096] The basic elements contained in the steel sheet according to the embodiment of the present disclosure are as described above. That is, the steel sheet according to the embodiment of the present disclosure contains the above elements in its chemical composition, and the remainder includes Fe and impurities as the basic. The so-called impurities are components mixed into the raw materials such as ore and scrap steel during the industrial production of steel sheets due to various reasons in the manufacturing process. For the steel sheet according to the embodiment of the present disclosure, it includes components that are not intentionally added.

[0097] On the other hand, in order to improve various properties, the steel sheet may further contain the following elements (optional elements) instead of Fe as needed. These elements may not necessarily be contained, so the lower limit is 0%.

[0098] [Ti: 0% to 0.200%, V: 0% to 1.00%, Nb: 0% to 0.100%, Cr: 0% to 2.00%, Ni: 0% to 1.00%, Cu: 0% to 1.00% , Co: 0% to 1.00%, Mo: 0% to 1.00%, W: 0% to 1.00%, B: 0% to 0.0100%, Sn: 0% to 1.00% and Sb: 0% to 1.00%]

[0099] Ti (titanium), V (vanadium), Nb (niobium), Cr (chromium), Ni (nickel), Cu (copper), Co (cobalt), Mo (molybdenum), W (tungsten), B (boron), Sn (tin) and Sb (antimony) are all elements effective for increasing the strength of steel sheets. Therefore, one or more of these elements may be contained as needed. However, if these elements are contained excessively, the effect is saturated, and the cost is increased in vain. Therefore, the contents are set to Ti: 0% to 0.200%, V: 0% to 1.00%, Nb: 0% to 0.100%, Cr: 0% to 2.00%, Ni: 0% to 1.00%, Cu: 0% to 1.00%, Co: 0% to 1.00%, Mo: 0% to 1.00%, W: 0% to 1.00%, B: 0% to 0.0100%, Sn: 0% to 1.00%, Sb: 0% to 1.00%. In order to obtain sufficient effects, the content of each element may be 0.005% or more or 0.010% or more. In particular, the B content may be 0.0001% or more or 0.0005% or more.

[0100] [Ca: 0% to 0.0100%, Mg: 0% to 0.0100%, Ce: 0% to 0.0100%, Zr: 0% to 0.0100%, La: 0% to 0.0100%, Hf: 0% to 0.0100%, Bi: 0% to 0.0100%, and REM other than Ce and La: 0% to 0.0100%]

[0101] Ca (calcium), Mg (magnesium), Ce (cerium), Zr (zirconium), La (lanthanum), Hf (hafnium) and REM (rare earth elements) other than Ce and La are elements that contribute to the fine dispersion of inclusions in steel, and Bi (bismuth) is an element that can reduce the microsegregation of substitutional alloying elements such as Mn and Si in steel. Since each of these elements contributes to improving the workability of the steel sheet, one or more of these elements may be contained as needed. However, excessive inclusion causes deterioration of ductility. Therefore, the content is set to 0.0100% or less. In addition, in order to obtain a sufficient effect, the content of each element may be 0.0005% or more or 0.0010% or more.

[0102] In the steel plate according to the embodiment of the present disclosure, the remainder other than the above elements includes Fe and impurities. That is, the chemical composition of the steel plate according to the embodiment of the present disclosure includes the basic elements, and the remainder includes Fe and impurities, or includes the basic elements and further includes one or more of the arbitrary elements, and the remainder includes Fe and impurities.

[0103] "Microstructure inside the steel plate"

[0104] Next, the internal structure (microstructure) of the steel plate according to the embodiment of the present disclosure will be described.

[0105] In the steel plate according to the embodiment of the present disclosure, the microstructure at the depth position (position of 1 / 4 thickness) from the surface is specified. In the present embodiment, the range from the position of the depth (1 / 8 thickness) from the surface to the position of the depth (3 / 8 thickness) from the surface, centered at the depth position (1 / 4 thickness) from the surface, is regarded as the depth position (1 / 4 thickness) from the surface.

[0106] [Ferrite: 0% to 50%]

[0107] Ferrite is a soft structure with excellent ductility. In order to increase the elongation of the steel sheet, it can also be contained according to the required strength or ductility. However, if it is contained excessively, it is difficult to ensure the desired strength of the steel sheet. Therefore, the volume fraction of ferrite is set to 50% or less. The volume fraction of ferrite can also be 45% or less, 40% or less, or 35% or less. The volume fraction of ferrite can also be 0%, for example, it can also be 3% or more, 5% or more, or 10% or more.

[0108] [Retained austenite: 6% to 30%]

[0109] Retained austenite is a structure that improves the ductility of the steel sheet based on the TRIP effect of the phase transformation into martensite through processing-induced phase transformation during deformation of the steel sheet. Therefore, the volume fraction of retained austenite is set to 6% or more. The volume fraction of retained austenite can also be set to 8% or more or 10% or more. The higher the volume fraction of retained austenite, the higher the elongation of the steel sheet, but to obtain a large amount of retained austenite, a large amount of alloying elements such as C is required. Therefore, the volume fraction of retained austenite is set to 30% or less. The volume fraction of retained austenite can also be 25% or less or 20% or less.

[0110] [Bainite: 5% to 60%]

[0111] In the present embodiment, in order to suppress the formation of coarse tempered martensite, bainite transformation is locally performed before martensite transformation. Therefore, the volume fraction of bainite is set to 5% or more. The volume fraction of bainite may also be 8% or more, 12% or more, 13% or more, or 15% or more. In addition, in order to properly ensure the balance between strength and ductility, the volume fraction of bainite is set to 60% or less. The volume fraction of bainite may also be 50% or less, 40% or less, or 35% or less.

[0112] [Tempered martensite: 5% to 50%]

[0113] Tempered martensite is a high-strength and tough structure. In order to balance strength, ductility, and hole expansion at a higher level, the volume fraction of tempered martensite is set to 5% or more. The volume fraction of tempered martensite can also be 10% or more, 15% or more, or 20% or more. In addition, in order to properly ensure the balance between strength and ductility, the volume fraction of tempered martensite is set to 50% or less. The volume fraction of tempered martensite can also be 45% or less, 40% or less, or 30% or less.

[0114] [Primary martensite: 0% to 10%]

[0115] In the present embodiment, the so-called fresh martensite refers to martensite that has not been tempered (martensite that does not contain carbides). Since fresh martensite is a brittle structure, it becomes the starting point of fracture during plastic deformation, causing the local ductility of the steel plate to deteriorate. Therefore, the volume fraction of fresh martensite is set to 10% or less. The volume fraction of fresh martensite is preferably 8% or less or 5% or less. From the viewpoint of suppressing the degradation of local ductility, the volume fraction of fresh martensite is ideally 0%, but the volume fraction of fresh martensite may also be 1% or more or 2% or more.

[0116] [Pearlite: 0% to 5%]

[0117] Pearlite is a structure containing hard and coarse cementite, which becomes the starting point of fracture during plastic deformation and deteriorates the local ductility of the steel plate. Therefore, the volume fraction of pearlite is set to 5% or less. The volume fraction of pearlite is preferably 3% or less or 2% or less. From the viewpoint of suppressing the deterioration of local ductility, the volume fraction of pearlite may also be 0%.

[0118] [At a depth of 1 / 4 of the plate thickness from the surface of the steel plate, the number of retained austenites having an aspect ratio of 2.0 or more accounts for 50% or more of the total retained austenite]

[0119] During forming, the retained austenite is transformed into martensite by process-induced phase transformation. When the retained austenite is transformed into martensite, when the process-induced martensite is adjacent to the soft ferrite, bainite and tempered martensite, a large hardness difference is generated between them. Such a large hardness difference becomes the cause of cracking in the early stage of deformation when forming such as hole expansion or stretch flange forming. In TRIP steel containing retained austenite, it is inevitable to generate such a hardness difference. However, by controlling its dispersion state, continuous crack propagation can be suppressed.

[0120] When the aspect ratio of the retained austenite is greater than 2.0, its morphology is lath-shaped. Since the retained austenite is the untransformed region after annealing, when the retained austenite is lath-shaped, the adjacent soft ferrite, bainite and tempered martensite are also lath-shaped. Such a lath-shaped organizational morphology is not easily affected by Mn segregation, so it is difficult to form a banded distribution of retained austenite. When the volume fraction of the retained austenite with an aspect ratio of less than 2.0 is greater than 50%, the volume fraction of the lath-shaped organization is not sufficient, and sufficient toughness cannot be obtained after press forming. Therefore, the ratio of the number of retained austenite with a lath-shaped morphology having an aspect ratio of greater than 2.0 is set to more than 50% of the total number of retained austenite, preferably more than 60%.

[0121] Here, the so-called aspect ratio of retained austenite is the value obtained by dividing the length of the major axis of the equivalent ellipse of the retained austenite grain by the length of the minor axis. The so-called equivalent ellipse is an ellipse with an area equal to that of the retained austenite grain and a maximum length L2 of the retained austenite grain as the length of its major axis. Even if the retained austenite grain has a complex shape, the aspect ratio (L2 / L1) of the retained austenite grain can be obtained from the length L1 of the minor axis and the length L2 of the major axis of its equivalent ellipse.

[0122] [At a depth of 1 / 4 of the plate thickness from the surface of the steel plate, the number density of inclusions and precipitates with a particle size of 1 μm or more is 30 / mm 2 the following]

[0123] The number density of inclusions and precipitates with a particle size of 1 μm or more present in the steel sheet is set to 30 pieces / mm 2 Here, the particle size of inclusions and precipitates is the equivalent circle diameter converted from the area of ​​the inclusions and precipitates. The inclusions are Al-based and Ti-based oxides, and the representative oxides are Al 2 O 3 . In addition, the precipitates are Ti-based and Al-based precipitates, among which the representative large-sized precipitates are nitrides such as TiN and AlN. In particular, TiN is coarsened due to its generation at high temperatures. These inclusions and precipitates are all hard, so if coarse inclusions and precipitates with a particle size of 1 μm or more among these inclusions and precipitates are present in large quantities in the steel plate, the toughness of the parts will deteriorate during a car collision. Therefore, the number density of inclusions and precipitates with a particle size of 1 μm or more present in the steel plate is set to 30 pieces / mm 2 Among the inclusions and precipitates, inclusions and precipitates having a particle size of less than 1 μm are not particularly limited because they have little influence on the toughness of the part after press forming.

[0124] [At a depth of 1 / 20 of the plate thickness from the surface, the average interval between Mn-concentrated portions in the direction perpendicular to the rolling direction is 300 μm or less]

[0125] At a depth of 1 / 20 of the plate thickness from the surface, the average spacing of the Mn concentrated areas in the direction perpendicular to the rolling direction (plate width direction) is set to be less than 300μm. Solidification segregation corresponding to the primary spacing of the dendrite arms during solidification occurs in the plate width direction, but by controlling the solidification and refining the primary spacing of the dendrite arms, the average spacing of the Mn concentrated areas can be controlled to be less than 300μm. If the above solidification control is not sufficient and the primary spacing of the dendrite arms in the slab is enlarged, Mn cannot be fully diffused during the cooling of the slab and the heating in the hot rolling process, and the Mn concentrated areas remain, so that the average spacing of the Mn concentrated areas is greater than 300μm.

[0126] If the average interval between the Mn concentrated portions exceeds 300 μm, it will be difficult to control the deterioration of toughness.

[0127] Here, the depth position of 1 / 20 of the plate thickness from the surface refers to the range from the position of 1 / 40 of the plate thickness (1 / 40 thickness) to the position of 3 / 40 of the plate thickness (3 / 40 thickness) from the surface.

[0128] The lower limit of the average interval of the Mn concentrated portions is not limited, but since it is not easy to set it below 100 μm, it may be set to 100 μm or more.

[0129] [At a depth of 1 / 20 of the plate thickness from the surface, the standard deviation of the Mn concentration in the retained austenite is 0.40% or less]

[0130] By setting the standard deviation of the Mn concentration in retained austenite in mass % (hereinafter sometimes referred to as the standard deviation of the Mn concentration) to 0.40% or less, the toughness during a car collision can be improved. When the standard deviation of the Mn concentration in retained austenite is large (error is large), since the retained austenite can be divided into a region with a low Mn concentration where a work-induced transformation is easy to occur and a region with a high Mn concentration where a work-induced transformation is difficult to occur (because Mn is an austenite-forming element), a difference in hardness occurs during a car collision, and the toughness decreases.

[0131] [Vickers hardness Hv at a depth of 30 μm from the surface sur The ratio of the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface satisfies Hv sur / [Hv]≤0.80]

[0132] In at least one surface, preferably, in either of the surface on one side and the surface on the other side (i.e., the surface and the back side), by softening the hardness at a position 30 μm from the surface of the steel plate along the plate thickness direction compared with the hardness at a position 1 / 4 into the plate thickness direction from the surface, the absorption energy during a car collision can be further improved, so it is preferred. In particular, in high-strength steel plates with a tensile strength of 980 MPa or more, fracture sometimes occurs at an early stage because they cannot withstand the strain imparted to the surface of the steel plate during a collision of parts. Therefore, in order to suppress fractures caused by the strain on the surface of the steel plate, softening the surface of the steel plate becomes an effective means. Since the Vickers hardness can be measured by measuring the indentation generated on the steel plate by the indenter load, the hardness at a position 30 μm from the surface at which a stable surface hardness can be obtained technically is defined as the surface hardness Hv. sur In addition, the ratio to the representative hardness in the steel plate is important, so by setting the ratio to the hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface to 0.80 or less, the bending properties can be improved, further improving the collision performance of automobile parts.

[0133] [Plating on the surface]

[0134] The steel sheet may also have a coating on the surface of the steel sheet. In the case where corrosion resistance is required due to the use environment of the steel material, there is no problem even if a coating mainly composed of zinc (containing more than 50% by mass of zinc) is formed on at least one surface, preferably on both surfaces. The coating is preferably a hot-dip galvanized layer or an alloyed hot-dip galvanized layer having any composition known to those skilled in the art, and may contain elements such as Al in addition to Zn. In addition, the amount of the coating is not particularly limited and may be a normal amount.

[0135] The microstructure fraction of the steel plate, the aspect ratio of retained austenite, and the number density of inclusions and coarse precipitates can be evaluated by SEM-EBSD (electron backscatter diffraction), SEM secondary electron image observation, and X-ray diffraction.

[0136] First, the sample was collected from the plate thickness section parallel to the rolling direction of the steel plate as the observation surface. After the observation surface was finished to a mirror surface by mechanical grinding, it was electrolytically polished. Next, the magnification was set to 3000 times in the observation field of the observation surface with a range of 1 / 8 to 3 / 8 thickness centered on the 1 / 4 thickness of the base steel plate surface, and a total of 2.0×10 - 9 m 2 The area above is analyzed by SEM-EBSD method for crystal structure and orientation. In the analysis of the data obtained by EBSD method, Ver.6.0 or above of "OIM Analysys" produced by TSL is used. In addition, the distance (step) between evaluation points is set to 0.03-0.20 μm. The area judged as FCC iron from the observation results is taken as retained austenite to obtain the area fraction of retained austenite. The area fraction is regarded as the volume fraction. In addition, the boundary with a crystal orientation difference of more than 15 degrees is taken as the grain boundary to obtain a crystal grain boundary map. For the retained austenite obtained by the crystal grain boundary map, OIM Analysis can be used to measure the minor axis, major axis and equivalent circle diameter, and the aspect ratio of the retained austenite is determined from the measurement results.

[0137] Next, the same sample that was observed by EBSD is etched with nitric acid, and the same field of view observed by EBSD is observed by secondary electron image. In order to observe the same field of view during EBSD measurement, it is best to pre-mark Vickers hardness indentations. From the obtained secondary electron image, "ferrite", "bainite", "tempered martensite", "primary martensite and / or retained austenite", and "pearlite" are distinguished, and the area fraction of each is measured, and the obtained area fraction is regarded as the volume fraction.

[0138] When distinguishing the organization, the area with a lower organization in the grain and cementite having multiple variants and precipitated is judged as tempered martensite. The area where cementite precipitates in a thin flake shape is judged as pearlite. The area with relatively low brightness in the remaining part and no lower organization is found is judged as ferrite. The area with high brightness and no lower organization is found by corrosion is judged as primary martensite and / or residual austenite. The area that does not meet any of the above areas is judged as bainite. The volume fraction of each organization is obtained by calculating the area fraction of each organization by the point counting method. The volume fraction of primary martensite can be obtained by subtracting the area fraction of residual austenite obtained by the above measurement from the area of ​​the area where the above lower organization is not found after corrosion.

[0139] The number density of inclusions and coarse precipitates was measured by secondary electron imaging. During the observation, 2.0×10 -9 m 2 The above viewing area is observed for n = 20 viewing fields for each manufacturing condition. Regarding the particle size, the area of ​​each inclusion and precipitate obtained by image analysis can be converted into an equivalent circle particle size, and the diameter is used as the particle size of each inclusion and precipitate. The number of inclusions and precipitates with a particle size of 1 μm or more is calculated and converted into the number per unit area (number density).

[0140] EPMA was used to measure the average interval of Mn concentrated portions and the standard deviation of the Mn concentration in retained austenite.

[0141] The rolled surface of the steel plate was ground and polished to produce an analysis sample with an analysis surface at a depth of 1 / 20 of the plate thickness from the surface, and the Mn distribution was investigated by EPMA. The average interval of the Mn concentrated portion needs to be measured in a relatively wide range, so the 8mm line segment in the direction orthogonal to the rolling direction (plate width direction) was continuously measured at 1μm intervals. Regarding the concentration of each measurement point, the 1μm point was measured on the line segment from each measurement point along the rolling direction to 500μm, and the average value was taken. The average value of the Mn concentration in the entire measurement point of 8mm in the plate width direction was taken as Mnave, the maximum value was taken as Mnmax, and the area with a Mn concentration of (Mnave+Mnmax) / 2 or more was taken as the Mn concentrated area, and the average value of the interval of the Mn concentrated area was calculated. In addition, the Si concentration was also measured at each measurement point, and the Mn concentration in the area where Si was lower than the average Si concentration of the steel plate was regarded as the Mn concentration in the retained austenite, and its standard deviation was calculated.

[0142] [Mechanical properties]

[0143] When the steel sheet according to the embodiment of the present disclosure is assumed to be used as a steel sheet for automobiles, as mechanical properties, it is preferred that TS is 980 MPa or more and TS×E1×λ is 980 MPa or more. 0.5 / 1000 is 80 or above.

[0144] The tensile strength (TS) and total elongation (El) were measured by collecting JIS No. 5 tensile test pieces from a direction perpendicular to the rolling direction, setting the distance between evaluation points to 50 mm, setting the tensile speed to 10 mm / min, and conducting a tensile test in accordance with JIS Z2241 (2011).

[0145] The hole expansion ratio (λ) was measured by performing a hole expansion test in accordance with the "JFS T1001 hole expansion test method" with a punch diameter of 10 mm, a blanking clearance of 12%, and a punch shape of a conical punch with a tip angle of 60°.

[0146] [Plate thickness]

[0147] The plate thickness of the steel plate according to the embodiment of the present disclosure is not limited, and is, for example, 0.1 to 30 mm.

[0148] "Method for manufacturing steel plate"

[0149] Next, a method for producing a steel plate according to an embodiment of the present disclosure will be described.

[0150] The method for producing a steel sheet according to the embodiment of the present disclosure can be roughly classified into two types: a production method shown in the following (4) and a production method shown in (5).

[0151] (4) A method for manufacturing a steel plate, comprising the following steps:

[0152] A casting process, which casts the molten steel having the above chemical composition into a slab having a thickness of 200 to 300 mm;

[0153] A hot rolling step of forming a hot-rolled steel sheet by hot rolling the slab;

[0154] A coiling step of coiling the hot-rolled steel sheet at a temperature range of 25 to 680° C.

[0155] a cold rolling step of forming a cold rolled steel sheet by cold rolling the hot rolled steel sheet after the coiling step at a reduction ratio of 20% or more;

[0156] A first annealing step of performing a first annealing on the cold-rolled steel sheet;

[0157] A second annealing step of performing a second annealing on the cold-rolled steel sheet after the first annealing step; and

[0158] The soaking treatment step is to hold the cold-rolled steel sheet after the second annealing step in a temperature range of 260 to 450° C. for 10 to 1000 seconds.

[0159] (5) A method for manufacturing a steel plate, comprising the following steps:

[0160] A casting process, which casts the molten steel having the above chemical composition into a slab having a thickness of 200 to 300 mm;

[0161] A hot rolling step of hot rolling the slab at a finishing temperature of 850° C. or higher to form a hot rolled steel sheet;

[0162] A coiling step of coiling the hot-rolled steel sheet at a temperature range of 25 to 450° C.

[0163] A cold rolling step of forming a cold rolled steel sheet by cold rolling the hot rolled steel sheet at a reduction ratio of 30% or less as required;

[0164] A first annealing step of performing a first annealing on the hot-rolled steel sheet or the cold-rolled steel sheet; and

[0165] The soaking treatment step is to hold the hot-rolled steel sheet after the first annealing step in a temperature range of 260 to 450° C. for 10 to 1000 seconds.

[0166] <Casting process>

[0167] First, the casting process will be described in detail.

[0168] Regardless of which manufacturing method among the above (4) and (5) is used, the process of manufacturing slabs by casting is common. Molten steel with the above chemical composition is smelted by a known smelting method such as a converter or an electric furnace, the solidification rate at a depth of 10 mm from the surface of the molten steel is set to 100-1000°C / min, and the amount of molten steel poured per unit time is set to 2.0-6.0 tons / min, and the average cooling rate between the liquidus temperature and the solidus temperature of the surface part at a depth of 5 mm from the above molten steel surface is set to 4°C / sec or more for cooling, and casting is performed to form a slab with a thickness of more than 200 mm and less than 300 mm.

[0169] The casting method is not limited, but continuous casting is preferred from the viewpoint of productivity and the like.

[0170] [Solidification rate: 100°C / min or more and 1000°C / min or less]

[0171] The solidification rate at a depth of 10 mm from the surface of the molten steel in the casting process is set to be greater than 100°C / min and less than 1000°C / min. If the solidification rate is lower than 100°C / min, it is sometimes difficult to set the primary dendrite arm spacing at a depth of 1 / 20 of the slab thickness from the slab surface to less than 300 μm, and the bendability of the steel sheet cannot be improved, or the standard deviation of the Mn concentration cannot be set to less than 0.40%. If the standard deviation of the Mn concentration exceeds 0.40%, the proportion of areas with relatively low Mn concentration in the steel increases, so that, for example, the bainite transformation cannot be suppressed during the cooling process of the annealing process of the cold-rolled steel sheet. On the other hand, if the solidification rate exceeds 1000°C / min, surface cracking of the slab is sometimes induced.

[0172] [Steel pouring amount per unit time: 2.0 to 6.0 tons / minute]

[0173] If the amount of molten steel poured per unit time is less than 2.0 tons / minute, the heat supplied to the mold is reduced, and the length of the claws on the upper part of the solidified shell increases. Therefore, the surface of the slab is easy to capture mold powder, and sometimes the number density of inclusions and precipitates with a particle size of 1 μm or more on the surface of the steel plate exceeds 30 / mm. 2 Therefore, the amount of molten steel poured per unit time is set to be above 2.0 tons / minute. 2 O 3 、SiO 2 On the other hand, if the amount of molten steel poured per unit time exceeds 6.0 tons / minute, the flow of the molten steel is too large, and the surface of the slab is prone to capture alumina-based inclusions due to the entrapment of mold powder. Sometimes, the number density of inclusions and precipitates with a particle size of 1 μm or more on the surface of the steel plate exceeds 30 / mm. 2 Therefore, the amount of molten steel poured per unit time is set to 6.0 tons / minute or less.

[0174] [The average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the molten steel surface is 4°C / sec or more]

[0175] The solidification process is in progress between the liquidus temperature and the solidus temperature, so Ti, Al, N, etc. are segregated in the molten steel, and TiN and AlN begin to precipitate and grow at the solidification interface. Therefore, if the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the slab surface is lower than 4°C / second, the low cooling rate causes the segregation of the molten steel components to develop, promoting the formation of precipitation nuclei, and also promoting the grain growth of the precipitates after precipitation. Sometimes, the number density of inclusions and precipitates with a particle size of 1 μm or more on the surface of the steel plate exceeds 30 / mm 2. Therefore, the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the slab surface is set to be 4°C / second or more. From the viewpoint of suppressing the formation of precipitates on the surface of the steel plate, it is preferred that the above average cooling rate is high, so the upper limit of the above average cooling rate does not need to be specifically stipulated, but if the cooling rate is too fast, there is a possibility of cracking of the slab, so it is preferred to set the average cooling rate to be 100°C / second or less.

[0176] [Slab thickness: 200 mm or more and 300 mm or less]

[0177] The slab thickness is set to be 200 mm or more and 300 mm or less. If the slab thickness is less than 200 mm, it is difficult to obtain the desired structure. On the other hand, if the slab thickness exceeds 300 mm, it is difficult to set the average spacing of the Mn concentrated portion extending in the rolling direction at a depth of 1 / 20 of the plate thickness from the steel plate surface to be less than 300 μm in the direction perpendicular to the rolling direction. In addition, if the slab thickness exceeds 300 mm, the surface and internal temperatures increase during heating, and the specified structure cannot be obtained at a position of 1 / 4 thickness in the steel plate.

[0178] <Hot rolling process>

[0179] In any of the above manufacturing methods (4) and (5), the conditions of the hot rolling process until the finish rolling are the same, and the slab having the above chemical composition is heated before the hot rolling.

[0180] [Average heating rate between Ac1 and Ac1+30°C: 2 to 50°C / min]

[0181] In this method, the average heating rate of the slab between Ac1 and Ac1+30°C during the heating of the slab before hot rolling is controlled to be 2 to 50°C / min. The dual-phase (austenite and ferrite) temperature region just above Ac1 is particularly prone to the distribution of alloy elements between austenite and ferrite. Therefore, when the slab is reheated, the temperature region is heated at a relatively fast average heating rate of more than 2°C / min. This is because if the average heating rate is lower than 2°C / min, Mn is distributed between austenite and ferrite during heating, making it difficult to keep the standard deviation of the Mn concentration below 0.40%. For example, the average heating rate may also be 4°C / min or more.

[0182] On the other hand, when rapid heating is performed such that the average heating rate is higher than 50°C / min, the temperature distribution in the thickness direction of the slab becomes uneven and thermal stress occurs. In this case, undesirable conditions such as thermal deformation of the slab may occur. For example, the above-mentioned average heating rate may be less than 40°C / min, less than 30°C / min, less than 20°C / min, or less than 10°C / min.

[0183] The Ac1 point can be calculated by the following formula: In the following formula, the mass % of the element is substituted for the symbol of the element. The element not contained is substituted for 0 (mass %).

[0184] Ac1(℃)=723-10.7×Mn-16.9×Ni+29.1×Si+16.9×Cr

[0185] [Heating the slab at 1200°C or above for more than 20 minutes]

[0186] Keeping the temperature at high temperature for a long time is effective for alleviating Mn segregation. Mn is a substitutional element, so its diffusion rate is very slow, and it starts to diffuse when heated to a high temperature of 1200°C or higher. By heating to 1200°C or higher and keeping it in this temperature range for more than 20 minutes, the standard deviation of the Mn concentration can be reduced to less than 0.40%.

[0187] [Rough rolling]

[0188] In this method, for example, the heated slab is subjected to rough rolling before finish rolling in order to adjust the thickness of the slab. Such rough rolling is not particularly limited, but is preferably carried out at a total reduction ratio of 60% or more at 1050°C or more. If the total reduction ratio is less than 60%, the recrystallization in hot rolling is not sufficient, which sometimes leads to inhomogeneity of the hot rolled steel sheet structure. The above-mentioned total reduction ratio may be, for example, less than 90%.

[0189] The manufacturing conditions after the finish rolling in the hot rolling process are different between the above (4) and (5). Therefore, the manufacturing conditions of the above (4) will be described in detail.

[0190] [Finishing rolling using multiple rolling stands]

[0191] There is no particular limitation on the finishing rolling conditions. In the equipment configuration including multiple rolling mills commonly used by those skilled in the art, it is best to perform rolling in such a way that the final pass outlet temperature (finishing rolling temperature) reaches an austenite region of 800°C or above.

[0192] <Coiling process>

[0193] [Coiling hot-rolled steel sheets in a temperature range of 25 to 680°C]

[0194] The coiling temperature is set to 25-680°C. Even when water-cooled, it is actually difficult to be lower than 25°C which is room temperature, so it is set as the lower limit. However, depending on the chemical composition, the strength of the hot-rolled steel sheet is sometimes too large, which impairs the cold rolling properties, so it can be selected according to the choice of chemical composition and the subsequent capacity of the cold rolling mill. The coiling temperature can also be above 400°C or above 500°C. On the other hand, by setting the coiling temperature to below 680°C, the ferrite transformation and the distribution of alloying elements (especially Mn) between ferrite and austenite can be suppressed. The coiling temperature can also be below 650°C or below 600°C.

[0195] <Cold rolling process>

[0196] [Cold rolling of hot-rolled steel sheets at a reduction ratio (cold rolling ratio) of 20% or more]

[0197] In this method, the hot rolled steel sheet is cold rolled. The reduction ratio (cold rolling ratio) (cumulative reduction ratio) may be set to 25% or more or 30% or more. On the other hand, excessive reduction leads to excessive rolling load and increased cold rolling mill load. Therefore, the reduction ratio may be set to 75% or less or 70% or less.

[0198] Before cold rolling, pickling may be performed according to known conditions as required.

[0199] <First Annealing Step>

[0200] [First annealing of cold-rolled steel sheet]

[0201] In the first annealing step, the cold-rolled steel sheet is heated to a temperature of Ac3 (°C) or higher to form an austenite single phase, and after cooling, a lath structure mainly composed of bainite or martensite is formed. At this time, the formation of ferrite and pearlite generated by diffusion transformation needs to be controlled.

[0202] Specifically, the cooling is performed in such a manner that the average heating rate between Ac1 and Ac1+30°C is set to be above 0.5°C / second, the maximum heating temperature of Ac3 to 950°C is maintained for 1 second to 1000 seconds, the average cooling rate in the temperature range to 650°C is set to be above 1.0°C / second, and the cooling stop temperature is 25 to 450°C.

[0203] When heating the steel sheet, the average heating rate between 600°C and Ac1 (°C) is not particularly limited, and is preferably limited to 10.0°C / second or less, for example. If the average heating rate exceeds 10.0°C / second, the recrystallization of ferrite cannot be fully performed, and the elongation of the steel sheet is sometimes deteriorated. The average heating rate may also be 6.0°C / second or less. In addition, the lower limit of the average heating rate is not particularly limited, and for example, the average heating rate may also be 1.0°C / second or more.

[0204] [The average heating rate between Ac1 and Ac1+30°C is 0.5°C / sec or more]

[0205] The average heating rate between Ac1 and Ac1+30°C when heating the steel plate is set to be above 0.5°C / second. If the average heating rate between Ac1 and Ac1+30°C is lower than 0.5°C / second, there is a clear distribution of Mn between ferrite and austenite, so the amount of coarse primary martensite increases in the final structure after plastic strain. The average heating rate may also be above 1.0°C / second. There is no particular upper limit to the average heating rate, for example, the average heating rate may also be below 10.0°C / second.

[0206] [Hold at the maximum heating temperature of Ac3 to 950°C for 1 second to 1000 seconds]

[0207] In order to fully austenitize, the steel plate is heated to at least Ac3 (°C) and is subjected to a soaking treatment at this temperature (maximum heating temperature). However, if the heating temperature is excessively increased, not only will the toughness be deteriorated due to the coarsening of the austenite grain size, but also damage will be caused to the annealing equipment. Therefore, the maximum heating temperature is set to below 950°C, preferably below 900°C. If the soaking time is short, austenitization will not be fully carried out. Therefore, the soaking time is set to at least 1 second, preferably 30 seconds or 60 seconds. On the other hand, if the soaking time is too long, productivity is hindered. Therefore, the soaking time is set to less than 1000 seconds, preferably less than 500 seconds. It is not necessary to keep the steel plate at a constant temperature during soaking, and the temperature can also vary within the range that satisfies the above conditions.

[0208] [The average cooling rate in the temperature range to 650°C is 1.0°C / sec or more, and the cooling stop temperature is 25 to 450°C]

[0209] After holding at the maximum heating temperature, cooling is performed. If ferrite transformation begins during cooling from the maximum heating temperature, the characteristics will be significantly deteriorated. Therefore, the average cooling rate from the maximum heating temperature to 650°C, where ferrite transformation is likely to occur, is set to be 1.0°C / second or more. The average cooling rate may also be 5.0°C / second or more or 20.0°C / second or more.

[0210] The cooling stop temperature is set to a range of 25° C. to 450° C. in order to make the steel sheet structure after the first annealing step a structure having bainite or martensite as a main phase.

[0211] <Second Annealing Step>

[0212] [Second annealing of the cold-rolled steel sheet after the first annealing step]

[0213] In the second annealing step, after a lath-shaped structure mainly composed of bainite or martensite is formed in the first annealing step, the steel is heated again and then cooled to 250° C. or less.

[0214] [After holding at the highest heating temperature of Ac1+20°C or higher and lower than Ac3(°C) for 1 second to 1000 seconds, cool to below 250°C]

[0215] The microstructure of the steel plate after the first annealing process is mainly composed of bainite and martensite. Therefore, in the second annealing process, the steel plate is heated again to a maximum heating temperature of more than Ac1+20°C and less than Ac3(°C), and the desired austenite volume fraction is achieved by maintaining the temperature in this temperature range for 1 second to 1000 seconds. When the maximum heating temperature is lower than Ac1+20°C, the volume fraction of austenite that undergoes reverse transformation by heating is not sufficient, and the volume fractions of bainite, tempered martensite and retained austenite generated in the subsequent cooling and soaking treatment processes cannot meet the range of this embodiment. On the other hand, if heated to a temperature above Ac3(°C), the lath-shaped structure formed in the first annealing process completely disappears, so the aspect ratio of the retained austenite cannot be controlled to be above 2.0. The holding time in this temperature range needs to be at least 1 second, and the upper limit is set to 1000 seconds, which is industrially realistic.

[0216] In order to obtain the retained austenite volume fraction within the range of the present embodiment, the steel sheet heated to the maximum heating temperature needs to control the degree of bainite transformation or martensite transformation. Therefore, the steel sheet heated to the maximum heating temperature needs to be cooled to 250°C or less. If the cooling stop temperature exceeds 250°C, the bainite transformation cannot be fully performed during the holding in the subsequent soaking treatment step, and the martensite obtained during the cooling to 250°C or less cannot be tempered, and the desired volume fraction in the microstructure cannot be obtained.

[0217] <Heat treatment process>

[0218] [After the second annealing step, the cold-rolled steel sheet is kept in a temperature range of 260 to 450°C for 10 to 1000 seconds]

[0219] In order to obtain the prescribed volume fraction of bainite and retained austenite in the present embodiment, the steel sheet cooled to below 250°C in the second annealing step is heated and maintained in a temperature range of 260 to 450°C. By maintaining in this temperature range, the carbon atoms discharged due to the bainite transformation are concentrated in the untransformed austenite, so that the stability of the untransformed austenite is improved, thereby ensuring the desired amount of retained austenite. When the holding temperature of the soaking treatment step is lower than 260°C, the bainite transformation proceeds slowly, and ultimately not only the volume fraction of bainite is insufficient, but also the volume fraction of retained austenite is insufficient. On the other hand, when maintained at a high temperature higher than 450°C, not only the strength of bainite is reduced, but also carbides are generated in austenite, which reduces the C concentration in austenite, so that the volume fraction of retained austenite is insufficient during the final cooling. The holding time in this temperature range needs to be at least 10 seconds. If it is shorter than this time, the bainite transformation is not sufficient. Furthermore, it is industrially difficult to maintain a time of more than 1000 seconds, so this is set as the upper limit.

[0220] The cooling after holding in the soaking treatment step is not limited.

[0221] [When the maximum heating temperature is maintained for 1 second to 1000 seconds in at least one of the first annealing step and the second annealing step, the atmosphere log (PH 2 O / PH 2 ) satisfies -1.10≤log(PH 2 O / PH 2 )≤-0.07]

[0222] When decarburizing the surface layer of the steel sheet, it is preferred to increase the oxygen potential log (PH 2 O / PH 2 ). If the oxygen potential is lower than -1.10, the oxygen potential becomes insufficient, carbon removal cannot be performed, and the Vickers hardness Hv at a depth of 30 μm from the surface cannot be sufficiently reduced. sur (The surface layer cannot be softened). On the other hand, if the oxygen potential is higher than -0.07, iron itself begins to oxidize and cannot be formed into a product, so this is the upper limit. Decarburization can be performed in either the first annealing step or the second annealing step, or in both. Decarburization can improve bendability while reducing the strength of the steel sheet. Therefore, it is best to adjust the oxygen potential according to the required characteristics. log(PH 2 O / PH 2 ) may also be within the above range before heating to the maximum heating temperature.

[0223] Next, the details of the manufacturing conditions of (5) above will be described. The details will be described starting with the finish rolling in the hot rolling process which is different from the manufacturing conditions of (4) above.

[0224] [Finishing rolling using multiple rolling stands]

[0225] There is no particular limitation on the finishing rolling conditions. In the equipment configuration including multiple rolling mills commonly used by those skilled in the art, the final pass outlet temperature (finishing rolling temperature) needs to be set to above 850° C. When the finishing rolling temperature is lower than 850° C., the phase transformation of austenite due to processing is advanced, and high-temperature phase transformation phases such as ferrite are generated during cooling, and the lath-shaped structure cannot be fully formed.

[0226] [Coiling of hot-rolled steel sheet in a temperature range of 25 to 450°C (coiling process)]

[0227] The coiling temperature is set to 25 to 450°C. The upper limit temperature is different from 680°C in the manufacturing condition (4) above, in order to form the microstructure of the hot rolled steel sheet into a microstructure mainly composed of bainite or martensite in the manufacturing condition (5). Since a microstructure mainly composed of bainite cannot be formed when coiling at a temperature higher than 450°C, pearlite and the like are generated, this is set as the upper limit.

[0228] <Cold rolling process>

[0229] [If necessary, cold rolling is performed at a reduction ratio of 30% or less to form a cold-rolled steel sheet]

[0230] In order to increase the thickness accuracy and improve the flatness, the hot-rolled steel sheet after the coiling step may be cold-rolled.

[0231] However, when the reduction rate is too high, excessive strain is introduced, which promotes the recrystallization of ferrite during annealing heating, and the acicular structure derived from the lath cannot be maintained. Therefore, when cold rolling is performed, the reduction rate (cold rolling rate) in cold rolling is set to 30% or less. In addition, since the workability of the product deteriorates as the reduction rate increases, the reduction rate is preferably 10% or less, and more preferably 5% or less. Since cold rolling may not be performed, the lower limit of the reduction rate is 0%.

[0232] <First Annealing Step>

[0233] [First annealing of hot-rolled steel sheet or cold-rolled steel sheet]

[0234] As described above, in the coiling step, a microstructure mainly composed of bainite or martensite is formed. Therefore, after the coiling step, the hot-rolled steel sheet that has not been cold-rolled or the cold-rolled steel sheet that has been cold-rolled with a reduction ratio of 30% or less is subjected to heat treatment in the first annealing step.

[0235] [After holding at the highest heating temperature of Ac1+20°C or higher and lower than Ac3(°C) for 1 second to 1000 seconds, cool to below 250°C]

[0236] Through the phase transformation in the coiling process, the microstructure is mainly composed of bainite and martensite. Therefore, the desired austenite volume fraction is formed by maintaining the maximum heating temperature above Ac1+20°C and below Ac3(°C) for 1 second to 1000 seconds in the first annealing process. When the maximum heating temperature is lower than Ac1+20°C, the volume fraction of austenite that undergoes reverse phase transformation by heating is not sufficient, and the volume fractions of bainite, tempered martensite and retained austenite generated in the subsequent cooling and heat treatment processes cannot meet the desired range. On the other hand, if heated to a temperature above Ac3(°C), the lath-shaped structure formed in the first annealing process completely disappears, so that the aspect ratio of the retained austenite cannot be controlled to be above 2.0. The holding time in this temperature range needs to be at least 1 second, and the upper limit is set to 1000 seconds, which is industrially realistic.

[0237] In order to obtain the retained austenite volume fraction within the range disclosed in the present invention, the steel sheet heated to the maximum heating temperature needs to undergo bainite transformation or martensite transformation. Therefore, the steel sheet heated to the maximum heating temperature needs to be cooled to 250°C or less. If the cooling stop temperature exceeds 250°C, the bainite transformation cannot be fully performed during the holding in the subsequent soaking treatment step, and the martensite obtained by cooling to 250°C or less cannot be tempered, so that the desired volume fraction in the microstructure cannot be obtained.

[0238] <Heat treatment process>

[0239] [The hot-rolled steel sheet or cold-rolled steel sheet after the first annealing step is held in a temperature range of 260 to 450° C. for 10 to 1000 seconds]

[0240] In order to obtain the prescribed volume fraction of bainite and retained austenite in the present embodiment, the steel sheet cooled to below 250°C in the second annealing step is heated and maintained in a temperature range of 260 to 450°C. By maintaining in this temperature range, the carbon atoms discharged due to the bainite transformation are concentrated in the untransformed austenite, so that the stability of the untransformed austenite is improved, thereby ensuring the desired amount of retained austenite. When the holding temperature of the heat treatment step is lower than 260°C, the bainite transformation progresses slowly, and ultimately not only the volume fraction of bainite is insufficient, but also the volume fraction of retained austenite is insufficient. On the other hand, when maintained at a high temperature higher than 450°C, not only the strength of bainite is reduced, but also carbides are generated in austenite, which reduces the C concentration in austenite, thereby insufficient volume fraction of retained austenite during the final cooling. The holding time in this temperature range needs to be at least 10 seconds. If it is shorter than that, the bainite transformation is insufficient. Furthermore, it is industrially difficult to maintain a time of more than 1000 seconds, so this is set as the upper limit.

[0241] The cooling after holding in the soaking treatment step is not limited.

[0242] [In the first annealing step, when the highest heating temperature is maintained for 1 second to 1000 seconds, the atmosphere log (PH 2 O / PH 2 ) satisfies -1.10≤log(PH 2 O / PH 2 )≤-0.07]

[0243] When decarburizing the surface layer of the steel sheet, it is preferred to increase the oxygen potential log (PH 2 O / PH 2 ). If the oxygen potential is lower than -1.10, the oxygen potential becomes insufficient, carbon removal cannot be performed, and the Vickers hardness Hv at a depth of 30 μm from the surface cannot be sufficiently reduced. sur (The surface layer cannot be softened). On the other hand, if the oxygen potential is higher than -0.07, iron itself will begin to oxidize and products cannot be formed, so this is set as the upper limit. log(PH 2 O / PH 2 ) can also reach the above range before heating to the maximum heating temperature.

[0244] <Plating process>

[0245] The plating step will be described in detail.

[0246] In the present method, regardless of which of the manufacturing methods (4) and (5) is selected, a plating step of immersing the steel sheet in a plating bath can be performed as needed. In this way, a plating layer can be formed on the surface of the steel sheet. The plating step is preferably a hot-dip galvanizing step of immersing the steel sheet in a hot-dip galvanizing bath. When forming a hot-dip galvanized layer, immersion in the hot-dip galvanizing bath can be performed during cooling from the highest heating temperature to below 250°C in the annealing step before the soaking step, or it can also be performed after the soaking step. The temperature of the steel sheet at this time has little effect on the performance of the steel sheet, but if the difference between the temperature of the steel sheet and the plating bath temperature is too large, the plating bath temperature changes, which sometimes causes trouble in the operation. Therefore, it is best to set a step of reheating or cooling the steel sheet in the range of the plating bath temperature -20°C to the plating bath temperature +20°C. Hot-dip galvanizing can be performed according to conventional methods. For example, the plating bath temperature is preferably 440 to 470°C, and the immersion time is preferably less than 5 seconds. The plating bath preferably contains 0.08 to 0.2 mass % Al and the remainder Zn, but may contain Fe, Si, Mg, Mn, Cr, Ti, and Pb as impurities. In addition, it is preferred to control the unit area weight of the plating layer by a known method such as gas friction contact. The unit area weight is preferably 25 to 75 g / m per side. 2 .

[0247] [Alloying treatment]

[0248] For hot-dip galvanized steel sheets with hot-dip galvanized layers, alloying treatment can also be performed as needed. In this case, if the alloying treatment temperature is lower than 460°C, the alloying speed is slow, which not only damages productivity but also causes uneven alloying treatment, so the alloying treatment temperature is set to above 460°C. On the other hand, if the alloying treatment temperature exceeds 600°C, excessive alloying is performed, and sometimes the adhesion of the steel plate coating is deteriorated. In addition, the pearlite phase transformation develops, and sometimes the desired metal structure cannot be obtained. Therefore, the alloying treatment temperature is set to below 600°C.

[0249] In the case where a plating process and / or alloying process is performed after the soaking process or after the soaking process, the steel sheet is cooled to room temperature after the plating process and / or alloying process to form a final product. Tempering rolling may also be performed to flatten and straighten the steel sheet and adjust the surface roughness. In this case, in order to avoid deterioration of ductility, the elongation is preferably set to 2% or less.

[0250] Example

[0251] Next, an embodiment of the present invention is described. The conditions in the embodiment are an example of conditions used to confirm the feasibility and effect of the present invention. The present invention is not limited to this one example of conditions. The present invention can adopt various conditions as long as it does not deviate from the main purpose of the present invention and achieves the purpose of the present invention.

[0252] The following calculation formula was used to calculate the phase transformation temperatures Ac1 (°C) and Ac3 (°C) used in the manufacturing condition limitation. (The element symbol in the formula is the mass % of the element in the steel)

[0253] Ac1=723-10.7×Mn-16.9×Ni+29.1×Si+16.9×Cr

[0254] Ac3=912-230.5×C+31.6×Si-20.4×Mn-39.8×Cu-18.1×Ni-14.8×Cr+16.8×Mo

[0255] In Example 1, conditional examples are shown for the inventions related to the above-mentioned [1], [2], [3], [4], [6], [8], and

[10] . In Example 2, conditional examples are shown for the inventions related to the above-mentioned [1], [2], [3], [5], [7], [9], and

[11] .

[0256] (Example 1)

[0257] Steel having the chemical composition shown in Table 1 is cast to produce slabs of 200 to 300 mm thickness. In Table 1, the units are mass %, and the remainder other than the components shown in Table 1 includes Fe and impurities. These slabs are hot rolled according to the conditions shown in Tables 2-1 to 2-3 to produce hot-rolled steel plates. During hot rolling, rough rolling is carried out in a manner that the total reduction ratio reaches 60% to 90% at a temperature of 1050°C or above, and finishing rolling is carried out in a manner that the finishing temperature reaches 800°C or above through multiple rolling stands. Then, the hot-rolled steel plate is pickled to remove the oxide scale on the surface. Then, the cold rolling process and the first annealing process, the second annealing process, and the soaking treatment process are carried out according to the conditions described in Tables 2-1 to 2-6. The conditions for hot-dip galvanizing or further alloying before or after the soaking treatment process are recorded as hot-dip galvanizing.

[0258]

[0259] Table 2-1

[0260]

[0261] Words in boldface and underlined text are outside the scope of the present invention.

[0262] Table 2-2

[0263]

[0264] Table 2-3

[0265]

[0266] Words in boldface and underlined text are outside the scope of the present invention.

[0267] Table 2-4

[0268]

[0269] Words in boldface and underlined text are outside the scope of the present invention.

[0270] Table 2-5

[0271]

[0272] Words in boldface and underlined text are outside the scope of the present invention.

[0273] Table 2-6

[0274]

[0275] Words in boldface and underlined text are outside the scope of the present invention.

[0276] Next, for each steel plate obtained in this way, the microstructure within the range of 1 / 8 thickness to 3 / 8 thickness centered at a position 1 / 4 thickness from the surface was observed by the above method, and the volume fractions of ferrite, retained austenite, bainite, tempered martensite, fresh martensite, and pearlite were respectively investigated.

[0277] Furthermore, the above method was used to examine the ratio of the number of retained austenite having an aspect ratio of 2.0 or more in the range of 1 / 8 to 3 / 8 thickness centered at a position 1 / 4 thickness from the surface to the total retained austenite.

[0278] In addition, the above method was used to investigate the number density of inclusions and precipitates with a grain size of 1 μm or more in the range of 1 / 8 thickness to 3 / 8 thickness centered at a position 1 / 4 thickness from the surface, the average spacing of Mn concentrated areas at a depth of 1 / 20 of the plate thickness from the surface, and the standard deviation of the Mn concentration in the retained austenite.

[0279] Regarding mechanical properties, JIS No. 5 tensile test pieces were collected from a direction perpendicular to the rolling direction, and tensile tests were performed according to JIS Z 2241 (2011) to measure tensile strength (TS) and total elongation (El). The distance between evaluation points was set to 50 mm, and the tensile speed was set to 10 mm / min.

[0280] The hole expansion ratio (λ) was measured using the "JFS T1001 hole expansion test method" of the Japan Iron and Steel Federation standard. The punch diameter was set to 10 mm, the punch clearance was set to 12%, and the punch shape was set to a conical punch with a tip portion of 60°.

[0281] TS is 980MPa or more, and TS×El×λ 0.5 The samples with a value of / 1000 of 80 or more had good mechanical properties and were judged to have press formability suitable for use as automobile parts.

[0282] The toughness after the introduction of plastic strain (toughness after press forming) is evaluated as follows. A JIS No. 5 tensile test piece is collected from a direction perpendicular to the rolling direction, and a 5% plastic strain (pre-strain) is given by a tensile test. In order to simulate the aging hardening caused by the input heat during baking and coating, a heat treatment of 170°C × 20 minutes is performed. A Charpy test piece with a 2mm V-notch is collected from the parallel part of the tensile test piece after the heat treatment simulating the strain imparting and baking coating. Then, the Charpy test is performed at a test temperature of -20°C in accordance with JIS Z2242 (2018). The test piece with the Charpy absorbed energy after imparting strain / Charpy absorbed energy before imparting plastic strain exceeding 0.7 is judged as Very Good (VG), the test piece with a value of 0.5 to 0.7 is judged as Good (G), and the test piece with a value of less than 0.5 is judged as Bad (B). The evaluations of VG and G are considered qualified.

[0283] In addition, in order to measure the Vickers hardness Hv at a depth of 30 μm from the surface sur The ratio of the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the above surface is calculated from the average value of the Vickers hardness at three points at the depth of the embedded test specimen in the cross section at a load of 20 g in accordance with JIS Z2244 (2009). sur / [Hv].

[0284] The results are shown in Tables 3-1 to 3-4.

[0285] In the table, a cold-rolled steel sheet not subjected to galvanizing is described as CR, a hot-dip galvanized steel sheet is described as GI, and an alloyed hot-dip galvanized steel sheet is described as GA.

[0286] Table 3-

[0287]

[0288] Bold underlined words indicate outside the scope of the present invention.

[0289] Table 3-2

[0290]

[0291] Words in boldface and underlined text are outside the scope of the present invention.

[0292] Table 3-3

[0293]

[0294] Words in boldface and underlined text are outside the scope of the present invention.

[0295] Table 3-4

[0296]

[0297] The steel sheet of the example of the present invention has high strength, and has a good balance among strength, elongation and hole expandability, and has little deterioration in Charpy absorbed energy after plastic deformation (pre-straining) and heat treatment at 170°C for 20 minutes simulating baking coating.

[0298] On the other hand, in the comparative examples, steel sheets could not be produced, or any of the strength, the balance between strength, elongation and hole expandability, plastic deformation (pre-strain provision) and Charpy absorbed energy at 170°C for 20 minutes after simulated baking coating was poor.

[0299] In Example No. 9, since the solidification rate at a position 10 mm from the molten steel surface was high and cracks occurred in the slab, the subsequent steps of hot rolling could not be carried out.

[0300] In Example No. 13, since the solidification rate at a position 10 mm from the molten steel surface is slow, the average interval of the Mn concentrated portion at a depth of 1 / 20 is enlarged. As a result, the standard deviation of the Mn concentration increases, and in addition to the deterioration of the balance of mechanical properties, the deterioration of the Charpy absorbed energy is also aggravated.

[0301] In Example No. 18, since the amount of molten steel poured per unit time is small, the inclusions and precipitates captured near the surface of the slab during casting increase, thereby deteriorating the Charpy absorption energy.

[0302] In Example No. 19, since the amount of molten steel poured per unit time was large, the inclusions and precipitates captured near the surface layer of the slab due to the entrapment of mold powder increased. As a result, the Charpy absorption energy deteriorated.

[0303] In Example No. 17, since the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer of the molten steel at a depth of 5 mm was too slow, the grain growth of inclusions and precipitates was promoted during the solidification process, resulting in deterioration of the Charpy absorption energy.

[0304] In Example No. 23, since the heating rate of the slab in Ac1 to Ac1+30°C is too slow, the Mn distribution according to α / γ is carried out during the temperature rise, which increases the standard deviation of the Mn concentration. As a result, the martensitic transformation temperature drops due to the local Mn concentration, and the volume fraction of the primary martensite increases. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy also deteriorates.

[0305] In Example No. 26, the slab heating temperature was low, so Mn could not be fully homogenized, and the volume fraction of fresh martensite increased and the standard deviation of Mn concentration increased. As a result, the balance of mechanical properties deteriorated and the Charpy absorption energy also deteriorated.

[0306] In Example No. 27, since the heating time of the slab at 1200° C. or higher was short, Mn could not be sufficiently homogenized, and the standard deviation of the Mn concentration increased. As a result, the balance of mechanical properties deteriorated and the Charpy absorption energy also deteriorated.

[0307] In Example No. 5, since the coiling temperature during hot rolling was high, Mn distribution occurred during phase transformation after coiling, which increased the standard deviation of Mn concentration. As a result, the balance of mechanical properties deteriorated and the Charpy absorption energy also deteriorated.

[0308] In Example No. 31, the average heating rate between Ac1 and Ac1+30° C. in the first annealing step was slow, so the standard deviation of the Mn concentration increased. As a result, the balance of mechanical properties deteriorated and the Charpy absorption energy also deteriorated.

[0309] In Example No. 15, since the maximum heating temperature in the first annealing step is low, the microstructure after the first annealing step does not form a full lath structure. Therefore, the volume fraction of retained austenite is insufficient, or the volume fraction of primary martensite increases, so in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy is also deteriorated.

[0310] In Example No. 30, since the average cooling rate from the maximum heating temperature to 650°C in the first annealing step is slow, ferrite transformation occurs during cooling, and the microstructure after the first annealing step does not form a full lath structure. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorbed energy is also deteriorated.

[0311] In Example No. 3, since the cooling stop temperature in the first annealing step is high, a complete lath structure is not obtained during the subsequent holding, and the volume fraction of primary martensite in the final product increases, and the number ratio of retained austenite with an aspect ratio of 2.0 or more decreases. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorbed energy also deteriorates.

[0312] In Examples No. 7 and 40, since the maximum heating temperature in the second annealing step is low, the retained austenite obtained in the final product is reduced, and the balance of mechanical properties is deteriorated, and the Charpy absorbed energy is also deteriorated.

[0313] In Example No. 12, since the maximum heating temperature in the second annealing step was high, the lath structure formed in the first annealing step collapsed and the predetermined microstructure was not obtained. As a result, the balance of mechanical properties was deteriorated.

[0314] In Examples No. 11, 22, and 43, since the cooling stop temperature in the second annealing step is high, the volume fraction of tempered martensite is reduced, and as a result, bainite transformation cannot be fully performed during the subsequent holding, and the volume fraction of primary martensite generated during the final cooling is increased. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy is also deteriorated.

[0315] In Examples No. 4 and 39, since the holding temperature after the cooling is stopped in the soaking treatment process is high, cementite is generated in the retained austenite exposed to high temperature, resulting in instability. Therefore, the volume fraction of the retained austenite finally obtained is reduced. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy is also deteriorated.

[0316] In Examples No. 16 and 25, since the holding temperature after the cooling is stopped in the soaking treatment process is low, the bainite transformation cannot be fully carried out during the holding, and the amount of primary martensite generated during cooling is increased. As a result, the balance of mechanical properties is deteriorated. In Example 25, the Charpy absorbed energy is also deteriorated.

[0317] In Example No. 54, the holding temperature after the cooling stop in the soaking treatment step was low, so the volume fraction of bainite was insufficient. In addition, the volume fraction of retained austenite was excessive, so the balance of mechanical properties was deteriorated.

[0318] In Example No. 58, since the holding temperature after the cooling stop in the soaking treatment step was high, the bainite transformation progressed excessively and the volume fraction of bainite became excessive. Therefore, the balance of mechanical properties deteriorated.

[0319] In Example No. 44, cracks occurred in the slab due to the high total content of Si and Al, and therefore, the steps after hot rolling could not be performed.

[0320] In Example No. 45, the Ms point cannot be greatly reduced due to the low C content, and as a result, the volume fraction of retained austenite decreases and the number ratio of retained austenite having an aspect ratio of 2.0 or more decreases, thereby deteriorating the balance of mechanical properties.

[0321] In Example No. 46, since the total content of Si and Al is small, the concentration of carbon in the untransformed austenite is reduced, and as a result, the volume fraction of retained austenite is reduced, the volume fraction of pearlite is increased, and the number ratio of retained austenite with an aspect ratio of 2.0 or more is reduced. Therefore, the balance of mechanical properties is deteriorated.

[0322] In Examples No. 47 and No. 64, the Ms point was not lowered due to the low Mn content, and as a result, the volume fractions of ferrite and pearlite increased, the volume fractions of retained austenite and tempered martensite increased, and the number ratio of retained austenite having an aspect ratio of 2.0 or more decreased. Therefore, the tensile strength was not sufficient.

[0323] In Example No. 48, cracks occurred in the steel sheet during the cold rolling process due to the high Mn content, and therefore, the subsequent processes could not be carried out.

[0324] In Example No. 49, cracks occurred in the steel sheet during the cold rolling process due to the high C content, and therefore, the subsequent processes could not be carried out.

[0325] In Example No. 50, cracks occurred in the slab due to the high Si content, and therefore, the steps after hot rolling could not be performed.

[0326] In Example No. 51, cracks occurred in the slab due to the high Al content, and therefore, the steps after hot rolling could not be performed.

[0327] In Examples No. 2, 10, 14, 21, 29, 32, 34, 35, 36, 37, 38, 41, 42, 61, and 62, since the oxygen potential is increased in one or both of the first annealing step and the second annealing step, internal oxidation occurs near the surface layer of the steel sheet, and decarburization is promoted and softening occurs, so the Vickers hardness Hv at a depth of 30 μm from the surface is sur The ratio of the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface is reduced, and the Charpy absorbed energy is improved by improving the bendability.

[0328] (Example 2)

[0329] The same slab as in Example 1 is used to produce hot-rolled steel sheets by hot rolling according to the conditions shown in Tables 4-1 and 4-2. Then, the hot-rolled steel sheets are pickled to remove the oxide scale on the surface. During hot rolling, rough rolling is carried out in a manner such that the total reduction ratio at 1050°C or above reaches 60% to 90%. Then, cold rolling, the first annealing step, and the soaking treatment step are carried out according to the conditions shown in Tables 4-3 and 4-4. The conditions for hot-dip galvanizing before or after the soaking treatment step are recorded as hot-dip galvanizing. In addition, in order to straighten the shape, a portion of the hot-rolled steel sheet after pickling is cold rolled at a reduction ratio of 2%.

[0330] Table 4-1

[0331]

[0332] Words in boldface and underlined text are outside the scope of the present invention.

[0333] Table 4-2

[0334]

[0335] Words in boldface and underlined text are outside the scope of the present invention.

[0336] Table 4-3

[0337]

[0338] Words in boldface and underlined text are outside the scope of the present invention.

[0339] Table 4-4

[0340]

[0341] Words in boldface and underlined text are outside the scope of the present invention.

[0342] Tables 5-1 to 5-4 show the results of testing the steel sheets produced under the same conditions as in Example 1.

[0343] Table 5-1

[0344]

[0345] Words in boldface and underlined text are outside the scope of the present invention.

[0346] Table 5-2

[0347]

[0348] Words in boldface and underlined text are outside the scope of the present invention.

[0349] Table 5-3

[0350]

[0351] Words in boldface and underlined text are outside the scope of the present invention.

[0352] Table 5-4

[0353]

[0354] The steel sheets of the examples of the present invention have high strength, a good balance among strength, elongation and hole expandability, and small deterioration in plastic deformation and Charpy absorbed energy at 170° C. for 20 minutes after simulated baking painting.

[0355] In Example No. 73, since the solidification rate at a position 10 mm from the molten steel surface was high and cracks occurred in the slab, the subsequent steps of hot rolling could not be carried out.

[0356] In Example No. 77, since the solidification rate at a position 10 mm away from the molten steel surface is slow, the average spacing of the Mn concentrated portion at the 1 / 20 thickness position is enlarged. As a result, the standard deviation of the Mn concentration in the retained austenite increases. Therefore, in addition to the deterioration of the balance of mechanical properties, the deterioration of the Charpy absorption energy is also aggravated.

[0357] In Example No. 83, since the amount of molten steel poured per unit time was small, the inclusions and precipitates captured near the surface layer of the slab increased during casting, and thus the Charpy absorption energy deteriorated.

[0358] In Example No. 84, since the amount of molten steel poured per unit time was large, the inclusions and precipitates captured near the surface of the slab due to the entrapment of mold powder increased. As a result, the Charpy absorption energy deteriorated.

[0359] In Example No. 82, since the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer of the molten steel at a depth of 5 mm was too slow, the grain growth of inclusions and precipitates was promoted during the solidification process, causing the Charpy absorption energy to deteriorate.

[0360] In Example No. 92, since the heating rate of the slab in Ac1 to Ac1+30°C is too slow, the Mn distribution according to α / γ is performed during the temperature rise, which increases the standard deviation of the Mn concentration in the retained austenite. As a result, the martensitic transformation temperature due to the local Mn concentration decreases, and the volume fraction of the primary martensite increases. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy also deteriorates.

[0361] In Example No. 96, since the slab heating temperature was low, Mn could not be sufficiently homogenized, and the standard deviation of the Mn concentration in the retained austenite increased. As a result, the Charpy absorption energy deteriorated.

[0362] In Example No. 88, since the heating time of the slab at 1200°C or higher was short, Mn could not be sufficiently homogenized, and the standard deviation of the Mn concentration in the retained austenite increased. As a result, the balance of mechanical properties deteriorated and the Charpy absorption energy also deteriorated.

[0363] In Examples No. 67 and 105, since the finishing rolling temperature in hot rolling is low, the dislocation density in austenite immediately after hot rolling increases, and the ferrite transformation is promoted. Therefore, a lath-shaped structure cannot be obtained in the microstructure after hot rolling. As a result, the volume fraction of retained austenite is insufficient or the volume fraction of primary martensite increases, so that the balance of mechanical properties deteriorates and the Charpy absorption energy also deteriorates.

[0364] In Examples No. 72, 87, and 108, since the coiling temperature during hot rolling was high, ferrite was generated by phase transformation after coiling. Therefore, a fully lath-shaped structure could not be obtained in the microstructure after hot rolling. As a result, the volume fraction of primary martensite increased, and the balance of mechanical properties deteriorated, and the Charpy absorption energy also deteriorated.

[0365] In Example No. 79, since the reduction ratio is high, the ratio of the number of retained austenites having an aspect ratio of 2.0 or more is reduced. As a result, the Charpy absorbed energy is deteriorated.

[0366] In Example No. 76, since the maximum heating temperature in the first annealing step is low, the retained austenite obtained in the final product is reduced, and the balance of mechanical properties is deteriorated, and the Charpy absorbed energy is also deteriorated.

[0367] In Examples No. 68 and 95, the maximum heating temperature in the first annealing step was high, so the lath structure formed in the hot rolling step collapsed, and the ratio of the number of retained austenites with an aspect ratio of 2.0 or more decreased. As a result, the balance of mechanical properties deteriorated and the Charpy absorbed energy also deteriorated.

[0368] In Example No. 69, since the cooling stop temperature in the first annealing step is high, the volume fraction of tempered martensite is reduced, and as a result, bainite transformation cannot be fully performed during the subsequent holding, and the volume fraction of primary martensite generated during the final cooling is increased. As a result, in addition to the deterioration of the balance of mechanical properties, the Charpy absorption energy is also deteriorated.

[0369] In Example No. 81, since the holding temperature after the cooling is stopped in the soaking step is high, cementite is generated in the retained austenite exposed to high temperature and is unstable, so the volume fraction of the retained austenite finally obtained is reduced. As a result, the balance of mechanical properties is deteriorated.

[0370] In Examples No. 90 and 107, since the holding temperature after the cooling stop in the soaking treatment step is low, the bainite transformation cannot be fully performed during the holding, and the amount of fresh martensite generated during the final cooling increases. As a result, the balance of mechanical properties deteriorates and the Charpy absorption energy also deteriorates.

[0371] In Example No. 119, the holding temperature after the cooling stop in the soaking treatment step was low, so the volume fraction of bainite was insufficient. In addition, the volume fraction of retained austenite became excessive, so the balance of mechanical properties deteriorated.

[0372] In Example No. 121, since the holding temperature after the cooling stop in the soaking treatment step was low, the volume fraction of bainite was insufficient, and thus the balance of mechanical properties was deteriorated.

[0373] In Example No. 125, since the holding temperature after cooling is stopped in the soaking treatment step is high and the holding time after cooling is long, bainite transformation proceeds excessively and the volume fraction of bainite becomes excessive, thus deteriorating the balance of mechanical properties.

[0374] In Example No. 109, since the total content of Si and Al was high, cracks occurred in the slab, and therefore, the steps after hot rolling could not be carried out.

[0375] In Example No. 110, the Ms point cannot be greatly lowered due to the low C content, resulting in a low volume fraction of retained austenite and a small number of retained austenites having an aspect ratio of 2.0 or more. Therefore, the balance of mechanical properties is deteriorated.

[0376] In Example No. 111, since the total content of Si and Al is small, carbon concentration in the untransformed austenite is reduced, resulting in a low volume fraction of retained austenite and a small number ratio of retained austenite with an aspect ratio of 2.0 or more. Therefore, the balance of mechanical properties is deteriorated.

[0377] In Examples No. 112 and 131, the Ms point cannot be lowered due to the low Mn content, and as a result, the volume fractions of ferrite and pearlite increase, the volume fractions of retained austenite and tempered martensite increase, and the number ratio of retained austenite with an aspect ratio of 2.0 or more decreases. Therefore, the tensile strength is not sufficient.

[0378] In Example No. 113, cracks occurred in the steel sheet during the cold rolling process due to the high Mn content, and therefore, the subsequent processes could not be carried out.

[0379] In Example No. 114, cracks occurred in the steel sheet during the cold rolling process due to the high C content, and therefore, the subsequent processes could not be carried out.

[0380] In Example No. 115, cracks occurred in the slab due to the high Si content, and therefore, the steps after hot rolling could not be carried out.

[0381] In Example No. 116, cracks occurred in the slab due to the high Al content, and therefore, the steps after hot rolling could not be performed.

[0382] In Examples No. 66, 70, 74, 75, 80, 85, 86, 89, 94, 98, 99, 100, 101, 103, 104, 106, 117, 118, 120, 122, 123, 124, 126, 127, 128, and 129, since the oxygen potential is increased in the first annealing step, internal oxidation occurs near the surface layer of the steel sheet, and decarburization is promoted and softening occurs, so the Vickers hardness Hv at a depth of 30 μm from the surface is sur The ratio of the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface is reduced, and the Charpy absorbed energy is improved by improving the bendability.

[0383] The preferred embodiments and examples of the present invention have been described above, but these embodiments and examples are only examples within the scope of the main idea of ​​the present invention. Additions, omissions, substitutions and other changes to the structure can be made without departing from the scope of the main idea of ​​the invention. In other words, the present invention is not limited by the above description, but only by the attached claims, and of course, appropriate changes can be made within the scope of the claims.

Claims

1. A steel plate, wherein: The chemical composition contains by mass %: C: 0.150% to 0.400%, Si: 0.01% to 2.50%, Mn: 1.50% to 3.50%, P: 0.050% or less, S: 0.0100% or less, Al:0.001%~1.500%、 Si and Al: 0.50% to 3.00% in total, N: 0.0100% or less, O: 0.0100% or less, Ti: 0% to 0.200%, V:0%~1.00%、 Nb: 0% to 0.100%, Cr:0%~2.00%、 Ni: 0% to 1.00%, Cu: 0% to 1.00%, Co: 0% to 1.00%, Mo: 0% to 1.00%, W:0%~1.00%、 B:0%~0.0100%、 Sn: 0% to 1.00%, Sb: 0% to 1.00%, Ca: 0% to 0.0100%, Mg: 0% to 0.0100%, Ce: 0%~0.0100%, Zr:0%~0.0100%、 La: 0% to 0.0100%, Hf: 0%~0.0100%, Bi: 0% ~ 0.0100%, and REM other than Ce and La: 0% to 0.0100%, The remainder includes Fe and impurities; The microstructure at a depth of 1 / 4 of the plate thickness from the surface contains, in terms of volume fraction: Ferrite: 0%~50%, Retained austenite: 6% to 30%, Bainite: 5% ~ 60%, Tempered martensite: 5%~50%, Primary martensite: 0%~10%, Pearlite: 0% to 5%; At a depth of 1 / 4 of the plate thickness from the surface, the number ratio of the retained austenite with an aspect ratio of 2.0 or more in the total retained austenite is 50% or more, and the number density of inclusions and precipitates with a grain size of 1 μm or more is 30 pieces / mm 2 the following; At a depth of 1 / 20 of the plate thickness from the surface, the average interval of Mn concentrated portions in a direction perpendicular to the rolling direction was 300 μm or less, and the standard deviation of the Mn concentration in the retained austenite was 0.40% or less.

2. The steel plate according to claim 1, wherein: Vickers hardness Hv at a depth of 30 μm from the surface sur The ratio of the Vickers hardness [Hv] at a depth of 1 / 4 of the plate thickness from the surface satisfies the following formula (1); What? sur / [Hv]≤0.80 (1).

3. The steel plate according to claim 1 or 2, wherein: A plating layer is provided on the surface.

4. A method for manufacturing a steel plate, which is the method for manufacturing a steel plate according to claim 1, wherein: It has the following processes: A casting step, wherein the molten steel having the chemical composition of claim 1 is cast into a slab having a thickness of 200 to 300 mm; A hot rolling step of forming a hot-rolled steel sheet by hot rolling the slab; A coiling step of coiling the hot-rolled steel plate at a temperature range of 25 to 680° C. a cold rolling step of forming a cold rolled steel sheet by cold rolling the hot rolled steel sheet after the coiling step at a reduction ratio of 20% or more; A first annealing step of performing a first annealing on the cold-rolled steel sheet; A second annealing step of performing a second annealing on the cold-rolled steel sheet after the first annealing step; and a soaking treatment step of maintaining the cold-rolled steel sheet after the second annealing step in a temperature range of 260 to 450° C. for 10 to 1000 seconds; In the casting process, the solidification rate at a depth of 10 mm from the surface of the molten steel is set to 100 to 1000°C / min, the amount of molten steel poured per unit time is set to 2.0 to 6.0 tons / min, and the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the surface of the molten steel is set to 4°C / sec or more for cooling; In the hot rolling process, the average heating rate of the slab between Ac1 and Ac1+30°C is 2 to 50°C / min, and the slab is heated at 1200°C or above for more than 20 minutes before hot rolling; In the first annealing step, the average heating rate between Ac1 and Ac1+30°C is 0.5°C / s or more, and the maximum heating temperature of Ac3 to 950°C is maintained for 1 second to 1000 seconds, and the average cooling rate in the temperature range to 650°C is 1°C / s or more, and the cooling stop temperature is 25 to 450°C; In the second annealing step, the temperature is maintained at a maximum heating temperature of Ac1+20° C. or higher and lower than Ac3 for 1 second to 1000 seconds, and then cooled to 250° C. or lower.

5. A method for manufacturing a steel plate, which is the method for manufacturing a steel plate according to claim 1, wherein: It has the following processes: A casting step, wherein the molten steel having the chemical composition of claim 1 is cast into a slab having a thickness of 200 to 300 mm; A hot rolling step of forming a hot-rolled steel sheet by hot rolling the slab; A coiling step of coiling the hot-rolled steel sheet in a temperature range of 25 to 450° C. A cold rolling step of forming a cold rolled steel sheet by cold rolling the hot rolled steel sheet at a reduction ratio of 30% or less as required; A first annealing step of performing a first annealing on the hot-rolled steel sheet or the cold-rolled steel sheet; and a soaking treatment step of maintaining the hot-rolled steel sheet or the cold-rolled steel sheet after the first annealing step in a temperature range of 260 to 450° C. for 10 to 1000 seconds; In the casting process, the solidification rate at a depth of 10 mm from the surface of the molten steel is set to 100 to 1000°C / min, the amount of molten steel poured per unit time is set to 2.0 to 6.0 tons / min, and the average cooling rate between the liquidus temperature and the solidus temperature of the surface layer at a depth of 5 mm from the surface of the molten steel is set to 4°C / sec or more for cooling; In the hot rolling process, the average heating rate of the slab between Ac1 and Ac1+30°C is 2 to 50°C / min, and the slab is heated at 1200°C or above for more than 20 minutes before hot rolling, and after finishing the finish rolling at a temperature of 850°C or above, the slab is cooled at an average cooling rate of 10°C / sec or above to 600°C; In the first annealing step, the temperature is maintained at a maximum heating temperature of Ac1+20° C. or higher and lower than Ac3 for 1 second to 1000 seconds, and then cooled to 250° C. or lower.

6. The method for manufacturing a steel plate according to claim 4, wherein: In at least one of the first annealing step and the second annealing step, when the maximum heating temperature is maintained for 1 second to 1000 seconds, log (PH2O / PH2) of the atmosphere in the heating furnace is -1.10≤log (PH2O / PH2)≤-0.

07.

7. The method for manufacturing a steel plate according to claim 5, wherein: In the first annealing step, when the maximum heating temperature is maintained for 1 second to 1000 seconds, the atmosphere in the heating furnace log (PH2O / PH2) is -1.10≤log (PH2O / PH2)≤-0.

07.

8. The method for manufacturing a steel plate according to claim 4 or 6, wherein: A hot-dip galvanizing step is provided, wherein the cold-rolled steel sheet is immersed in a hot-dip galvanizing bath during cooling from the maximum heating temperature to 250° C. or less in the second annealing step before the soaking step to form a hot-dip galvanized steel sheet.

9. The method for manufacturing a steel plate according to claim 5 or 7, wherein: A hot-dip galvanizing step is provided, in which the hot-dip galvanized steel sheet is formed by immersing the hot-rolled steel sheet or the cold-rolled steel sheet in a hot-dip galvanizing bath during cooling from the maximum heating temperature to 250° C. or less in the first annealing step before the soaking step.

10. The method for manufacturing a steel plate according to claim 4 or 6, wherein: A hot-dip galvanizing step is provided for forming a hot-dip galvanized steel sheet by immersing the cold-rolled steel sheet after the soaking step in a hot-dip galvanizing bath.

11. The method for manufacturing a steel plate according to claim 5 or 7, wherein: A hot-dip galvanizing step is provided for forming a hot-dip galvanized steel sheet by immersing the hot-rolled steel sheet or the cold-rolled steel sheet after the soaking step in a hot-dip galvanizing bath.

Citation Information

Patent Citations

  • High strength thin steel sheet having excellent elongation and hole expansibility and method for producing the same

    JP2006104532A

  • High-strength cold-rolled steel sheet having excellent formability and method for manufacturing the same

    JP2013185196A

  • Transistor

    JP2020174217A

  • High-strength steel sheet and method for manufacturing same

    WO2013051238A1

  • Steel sheet

    WO2019186989A1